PEMBERDAYAAN INDUSTRI KERAJINAN SUVENIR KAYU TERDAMPAK PANDEMI DI KECAMATAN PEDAN KABUPATEN KLATEN - Eko Sri Haryanto; Tri Prasetyo Utomo (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2021)
ABSTRACT The Covid-19 pandemic has caused Micro, Small and Medium Enterprises (MSMEs) to experience a drastic decline in income, especially in tourist souvenirs. The impact is a reduction in the workforce and a decrease in people's income. The partner of this activity is a Luphy Craft souvenir belonging to Mr. Sriyanto. Souvenirs from Micro, Small and Medium Enterprises, among others; tourist souvenirs, wedding souvenirs and other event souvenirs. The purpose of this activity is so that partners can develop their businesses even though they are still in the midst of the Covid-19 Pandemic. The methods used include discussion, design training, making promotional media, making online media, creating marketplace accounts, making video profiles, simple management training and online sales training. The results of this community service activity are in accordance with the output that has been set at the beginning. This activity is not only beneficial for partners, but is also an implementation of the Tri Dharma Perguruan Tinggi, especially in the field of community service.